Portfolio Management in Times of Elevated Risk. Safe-Haven and Hedge Assets in CAPM Setting - Feder-Sempach, Ewa (Journal of Finance and Financial Law, 2024)
The purpose of the article. The purpose of the article is to present the safe-haven concept according to the latest academic literature and distinguish it from the hedge and diversifier terms that are sometimes used interchangeably by researchers and portfolio managers. The ultimate goal of the paper is to place the safe-haven and hedge assets in the portfolio theory setting by introducing the negative beta parameter as stated in the Capital Asset Pricing Model. According to the literature, this article proposes a few approaches to identify and characterize safe-haven assets and to discover the perspective and outline further research in the portfolio theory. Methodology. The work uses the method of descriptive and comparative analysis of literature, i.e., Systematic Literature Review (SLR). This method is used to present scientific overview of portfolio management when uncertainty rises to identify safe-haven and hedge assets. Results of the research. This paper aims to characterize and identify three main types of assets helping investors to reduce the portfolio risk: safe haven, hedge, and diversifier. It introduces an improved analytical framework of beta parameter and drawdown beta concept to contribute to the rapidly expanding research on portfolio theory. Lastly it depicts a trade-off effect, which is stronger in-crisis performance of safe-haven assets. The returns of safe-haven assets are more positive when the stock market returns are more negative that may safeguard the financial system.